2020
DOI: 10.6017/ital.v39i3.12211
|View full text |Cite
|
Sign up to set email alerts
|

Likes, Comments, Views

Abstract: This article presents a content analysis of academic library Instagram accounts at eleven land-grant universities. Previous research has examined personal, corporate, and university use of Instagram, but fewer studies have used this methodology to examine how academic libraries share content on this platform and the engagement generated by different categories of posts. Findings indicate that showcasing posts (highlighting library or campus resources) accounted for more than 50 percent of posts shared, while a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 4 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…Concise and informative sentences, varied images and writings. According to (Doney et al, 2020), there are various methods to measure the effectiveness of an instagram post, a large number of likes or comments may indicate positive signs for active engagement. Other ways to measure engagement and effectiveness include evaluating reach and impressions, or analyzing the content of comments (a type of qualitative measurements).…”
Section: Resultsmentioning
confidence: 99%
“…Concise and informative sentences, varied images and writings. According to (Doney et al, 2020), there are various methods to measure the effectiveness of an instagram post, a large number of likes or comments may indicate positive signs for active engagement. Other ways to measure engagement and effectiveness include evaluating reach and impressions, or analyzing the content of comments (a type of qualitative measurements).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, crowdsourcing posts, which ask users to engage with the post, gained the highest average number of likes and comments. On the other hand, the most frequently posted category, showcasing, gained the lowest average likes and near lowest comment count (Doney et al, 2020). Similarly, research following fashion brands and their posting categories found that posts that offered incentives for interacting saw increased interaction.…”
Section: Effects Of Posting Category On Engagementmentioning
confidence: 98%
“…Over 50% of businesses use Instagram as a means of advertising and sharing their brand (Alkhowaiter, 2016). Moreover, Instagram users who follow businesses on Instagram have the highest levels of commitment and interaction as opposed to other platforms (Doney et al, 2020). By utilizing Instagram, businesses can directly interact and connect with potential customers around the globe.…”
Section: Social Media Marketing and Instagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Instagram, the social media chosen for this study, was created in 2010, and in 2019, it reached the number of more than one billion active user accounts, and it is estimated that 90% of users follow at least one commercial account (Doney et al 2020). Instagram has a visual appeal of the images and videos that are shared, which is important for the promotion and sale of beauty products, in addition to being one of the social media most used by digital influencers (Almeida et al 2018).…”
Section: Social Media Usementioning
confidence: 99%